A Mid Cretaceous representative of the modern scatopsid genus Ectaetia (Diptera: Scatopsidae: Ectaetiinae) - Fate, Caitlin; Perrichot, Vincent; Nel, Andre (Zootaxa, 2013)
Ectaetia capdoliensis sp. n., first Cretaceous and oldest representative of the scatopsid subfamily Ectaetiinae, is described from the Late Albian / Early Cenomanian amber of southwestern France. This fossil demonstrates the remarkable morphological stability of these flies since at least the mid-Cretaceous. It suggests the presence of rotten wood under wet palaeoenvironment for the corresponding outcrop of Cadeuil.